Organización contable en la ferretería del Sr. Cuenca Quinde Darwin Rigoberto del cantón Catamayo, periodo del 01 de octubre al 31 de diciembre del 2023. - Sinche Cuenca, Helen Estefanía (2024)
The Curricular Integration or Thesis Work entitled ACCOUNTING ORGANIZATION IN MR. CUENCA QUINDE DARWIN RIGOBERTO'S HARDWARE STORE IN THE CATAMAYO CANTON, PERIOD FROM OCTOBER 1 TO DECEMBER 31, 2023, was carried out with the purpose of having adequate accounting organization taking into account the needs of the company to facilitate the control and recording of all operations and thus obtain current economic and financial information, thereby fulfilling the proposed objectives; therefore, a plan and chart of accounts adjusted to the needs of the hardware store were developed, which are duly codified and presented in an orderly manner together with the chart of accounts that evidences the nature of the accounts of assets, liabilities, equity, income, costs, and expenses, which serve as a basis for the development of accounting. Additionally, auxiliary formats were elaborated according to the company's requirements, including auxiliary documents for purchases and sales, accounts receivable and accounts payable auxiliaries, payroll and provisions, cash flow auxiliary, depreciation auxiliary; which facilitated the accounting process since the obtained information is more detailed and allows simplifying the registration of operations. In this way, the accounting process begins through the use of the perpetual inventory system where Kardex cards were made, important documents reflecting the movement of inputs and outputs of merchandise available for sale; then the initial inventory begins by collecting the inventory of merchandise and documents that support the assets, values, rights, and obligations of the company; next, the initial financial position was structured where the assets, liabilities, and equity of the company are reflected, with this, the journal was developed where the operations carried out by the hardware store were recorded orderly, the balance of the balances was developed in the general ledger, which serves as a basis for the subsequent preparation of the trial balance, 4 and the worksheet with its respective adjustments, a preliminary document that facilitates the preparation of financial statements. Finally, the income statement was developed, which shows the income, costs, and expenses incurred, the financial position statement where the assets, liabilities, equity are detailed and the profit obtained at the end of the accounting period is reflected, the cash flow statement where the cash inflows and outflows and their equivalents are recorded, records that reflect the economic and real situation of the company that help decision-making and the statement of changes in equity which reflects the variations that the net worth has undergone in the economic year.